ENSO Enhances Seasonal River Discharge Instability and Water Resource Allocation Pressure - Minxiang Zhu; Dan Yu; Yiqi Yu; Yi Zheng; Shaobin Li; Ximing Cai; Nengwang Chen (Water Resources Research)
Abstract The El Niño‐Southern Oscillation (ENSO) significantly disrupts Pacific Ocean watershed hydrology, affecting water supply reliability. However, the specific ways in which ENSO affects seasonal river discharge remain underexplored, presenting a significant gap in our understanding of climate‐water interactions. Our study reveals that ENSO exacerbates river discharge variability, evident in the dynamics of maximum rise (Dr) and fall (Df) in standardized discharge, and their duration (M). Notably, ENSO augments Dr but shortens M in major rivers like the Yangtze. Employing a novel metric, the Discharge Instability Index (DII), we find that DII surges by at least 69% in El Niño years, particularly in southwestern North American watersheds. Vegetation and precipitation emerge as pivotal in shaping the discharge response to ENSO. Predictive modeling with DII suggests an escalation in discharge instability under climate warming, with a 0.11%–9.46% increase. This insight calls for water managers to integrate ENSO‐induced seasonal variations into strategic planning, blending immediate actions like dam regulation with long‐term initiatives such as afforestation, to counteract climate‐induced water scarcity.